Operational conditions for successful partial nitrification in a sequencing batch reactor (SBR) based on process kinetics. Issue 6 (19th March 2017) - Liu, Xiaoguang; Kim, Mingu; Nakhla, George
ABSTRACT: The objective of this study is to analyze the factors affecting the performance of partial nitrification in a sequencing batch reactor (SBR) using kinetic models. During the 4-month operation, dissolved oxygen (DO) and influent ammonia concentration were selected as operating variables to evaluate nitrite accumulation. Stable partial nitrification was observed with two conditions, influent ammonia concentration of 190 mg N/L and a DO of 0.6–3.0 mg/L as well as influent ammonia concentration of 100 mg N/L and a DO of 0.15–2.0 mg/L with intermittent aeration. At a DO of 0.6–3.0 mg O2 /L and influent ammonia concentration of 90 mg N/L, nitrite-oxidizing bacteria growth was not suppressed. Kinetic parameters were determined or estimated with batch tests and model simulation. The kinetic model predicted the SBR performance well.